A method for preparing a controllable morphology palladium tin intermetallic compound

By preparing palladium-tin intermetallic compounds with controllable morphology through high-temperature pyrolysis and surface modification, the catalytic performance and stability issues of single-metal nanoenzyme materials were solved. This resulted in the water solubility and multi-enzyme catalytic activity of palladium-tin nanoenzymes, making them suitable for nanobiomedical research and disease diagnosis.

CN118904331BActive Publication Date: 2026-11-06HARBIN ENG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410943250.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2026-11-06
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

Existing single-metal nanozyme materials have poor catalytic performance and stability, bimetallic nanozyme materials have uncontrollable morphology during preparation, and palladium-tin nanozyme catalysts are insoluble in water.

Method used

Palladium-tin intermetallic compounds were prepared by high-temperature pyrolysis. By controlling the mass ratio of methylamine hydrochloride to tin acetate, palladium-tin intermetallic compounds with different morphologies were generated, and their water solubility was improved by modification with soybean lecithin.

Benefits of technology

A palladium-tin intermetallic compound with controllable morphology was prepared, exhibiting good catalytic performance, stability, and water solubility. It also possesses excellent near-infrared light absorption and various enzyme catalytic activities, making it suitable for nanobiomedical research and disease diagnosis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118904331B_ABST
    Figure CN118904331B_ABST
Patent Text Reader

Abstract

A method for preparing palladium-tin intermetallic compounds with controllable morphology is disclosed. This invention addresses the problems of poor catalytic performance and stability, and limited enzyme activity in existing single-metal nanozyme materials; it also solves the problems of uncontrollable morphology in existing bimetallic nanozyme materials and the insolubility of common palladium-tin nanozyme catalysts in water. The preparation methods include: 1. High-temperature pyrolysis to prepare palladium-tin intermetallic compounds; 2. Surface modification of the palladium-tin intermetallic compounds. This invention is used for the preparation of palladium-tin intermetallic compounds with controllable morphology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing palladium-tin intermetallic compounds. Background Technology

[0002] Nanozyme catalysts, due to their high surface area ratio, enzyme activity, and good biocompatibility, can serve as alternatives to natural enzymes. They have achieved groundbreaking progress in clinical medicine, food safety, environmental monitoring, and chemical production, particularly in areas such as bioanalysis, antibacterial, anti-inflammatory, and anticancer applications. In the field of bioanalysis, nanozyme-based colorimetric methods, electrochemical methods, and enzyme-linked immunosorbent assays (ELISA) are used to improve the sensitivity and specificity of detecting various substances (heavy metal ions, biomarkers, pathogenic microorganisms, antibodies, etc.).

[0003] Existing nanozyme catalysts are often composed of carbon-based materials, metals, and transition metal compounds. Generally, the structural characteristics of existing metal and metal oxide-based nanozymes can be broadly classified into single metals, metal alloys, metal oxides, metal core / shell nanostructures, and hybrid nanomaterials. Due to their excellent physicochemical properties (e.g., high surface energy, superior optical and photothermal conversion properties), as well as their low cost, high stability, and ease of storage, metal and metal oxide-based nanozymes are of significant guiding importance for in-depth research into their catalytic activity and mechanisms.

[0004] Single-metal nanozymes are typically noble metal nanomaterials that exhibit significant chemical stability under natural conditions. They usually possess sites that readily couple with various biomolecular ligands and antibodies, exhibit significant surface plasmon resonance (SPR) properties, and possess superior optical and photothermal conversion characteristics. However, bare single-metal nanoparticles (such as Ag and Pt) suffer from a single active site, making them unsuitable for complex catalytic reactions. Furthermore, single-metal nanozymes are prone to sintering at high temperatures, are susceptible to competitive adsorption by poisons, and exhibit poor resistance to CO2 and SO2 (i.e., catalytic activity decreases significantly in the presence of CO2 or SO2). They also tend to aggregate into nanoclusters, leading to reduced catalytic activity. Most importantly, most bare noble metal nanozymes (except gold) are biotoxic, thus limiting their application in clinical medicine.

[0005] In bimetallic nanozyme catalysts, adjacent bimetallic atoms provide co-adsorption sites for molecules, which can facilitate molecular activation by elongating chemical bonds or adjusting the adsorption layout. The strong interactions between bimetallic atoms help regulate the electronic structure, promoting the adsorption / desorption of intermediates. Furthermore, synergistic effects exist between bimetallic atoms, all of which contribute to highly efficient catalysis of complex reactions. Bimetallic nanozyme catalysts produce less CO2 during catalysis and exhibit higher CO2 tolerance. Compared to metal nanoparticles, bimetallic nanoparticles have lower bioactivity. They also generally lack genotoxicity, making them safer to use. However, due to the complexity of the structure of bimetallic nanozyme catalysts, structural inhomogeneity and uncontrollable morphology are common, and common palladium-tin nanozyme catalysts are insoluble in water. Summary of the Invention

[0006] This invention aims to address the problems of poor catalytic performance and stability, and limited enzyme activity in existing single-metal nanozyme materials; and to solve the problems of uncontrollable morphology in the preparation of existing bimetallic nanozyme materials and the insolubility of common palladium-tin nanozyme catalysts in water. Therefore, it provides a method for preparing palladium-tin intermetallic compounds with controllable morphology.

[0007] A method for preparing a palladium-tin intermetallic compound with controllable morphology, comprising the following steps:

[0008] I. Preparation of Palladium-Tin Intermetallic Compounds by High-Temperature Pyrolysis:

[0009] Under magnetic stirring, oleylamine, methylamine hydrochloride, palladium acetylacetone, and tin acetate were mixed uniformly to obtain mixed solution A. Under vacuum, mixed solution A was heated to 40℃~45℃ and kept at 40℃~45℃ for 20min~25min. The vacuum device was then turned off, nitrogen gas was introduced, and the temperature was kept at 55℃~60℃ for 30min~35min to form a homogeneous solution. Trioctylphosphine was added to the homogeneous solution, and the temperature was kept at 200℃~210℃ for 30min~35min to obtain mixed solution B. Mixed solution B was heated to 300℃~310℃ and reacted at 300℃~310℃ for 25min~30min. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, collected by centrifugation, and washed to obtain the palladium-tin intermetallic compound.

[0010] When the mass ratio of methylamine hydrochloride to tin acetate is (0-0.25):1, the palladium-tin intermetallic compound is composed of nanoparticles with a particle size of 5 nm to 10 nm.

[0011] When the mass ratio of methylamine hydrochloride to tin acetate is (0.5-0.75):1, the palladium-tin intermetallic compound is a short nanorod with a length of 30 nm to 35 nm.

[0012] When the mass ratio of methylamine hydrochloride to tin acetate is (1.25-1.5):1, the palladium-tin intermetallic compound is a nanorod with a length of 70 nm-75 nm.

[0013] When the mass ratio of methylamine hydrochloride to tin acetate is (2.5-2.75):1, the palladium-tin intermetallic compound is a nanorod with a length of 120 nm to 125 nm.

[0014] II. Surface modification of palladium-tin intermetallic compounds:

[0015] The palladium-tin intermetallic compound was dissolved in cyclohexane, and then a chloroform solution of soybean lecithin was added dropwise. The solvent was evaporated in a rotary evaporator under vacuum and at a temperature of 60℃~65℃ to obtain the soybean lecithin-modified palladium-tin intermetallic compound.

[0016] The beneficial effects of this invention are:

[0017] ① The present invention prepares a palladium-tin intermetallic compound bimetallic nanozyme catalyst with controllable morphology and size, which has good catalytic performance and stability.

[0018] ② The material is obtained in one step by high-temperature pyrolysis. Palladium acetylacetonate is used as the palladium source and tin acetate is used as the tin source. By controlling the amount of methylamine hydrochloride, palladium-tin intermetallic compounds with controllable morphology are generated by reaction under high temperature conditions.

[0019] ③ Both characterization experiments and density functional theory calculations confirm that structurally ordered palladium-tin intermetallic compounds possess excellent near-infrared light absorption and various enzymatic catalytic activities (such as catalase, peroxidase, and oxidase-like activities). Comparative experiments revealed that nanorods with higher specific surface areas exhibit superior performance. Therefore, morphology-controllable palladium-tin intermetallic compounds hold promise for applications in nanobiomedical research.

[0020] ④ Tin ions in palladium-tin intermetallic compounds have a high X-ray attenuation coefficient and can be used as contrast agents in computed tomography imaging, for disease diagnosis, and for real-time monitoring of the treatment process.

[0021] Therefore, the palladium-tin intermetallic compound involved in this invention has a controllable morphology, good stability and catalytic performance, and also has good photothermal and optical properties.

[0022] Instruction manual illustrations

[0023] Figure 1 This is a diagram illustrating the synthesis process of the soybean phospholipid-modified palladium-tin intermetallic compound in Example 1.

[0024] Figure 2TEM images and elemental mapping images of Pd2Sn NDs and Pd2Sn NRs prepared in step one of Example 1 at different magnifications;

[0025] Figure 3 TEM images and elemental mapping images of Pd2Sn SNRs and Pd2Sn LNRs prepared in step one of Example 1 at different magnifications;

[0026] Figure 4 High-resolution transmission electron microscopy images and lattice spacing measurements of Pd2SnNRs and Pd2SnNDs prepared in step one of Example 1.

[0027] Figure 5 The EDS measurement spectrum of Pd2SnNRs prepared in step one of Example 1;

[0028] Figure 6 The images shown are PXRD images of Pd2Sn NDs, Pd2Sn SNRs, Pd2Sn NRs and Pd2Sn LNRs prepared in step one of Example 1. a is Pd2Sn NRs and Pd2Sn NDs, b is a magnified view of a, and c is Pd2Sn LNRs and Pd2Sn SNRs.

[0029] Figure 7 XPS measurement spectra of Pd2SnNRs and Pd2SnNDs prepared in step one of Example 1;

[0030] Figure 8 High-resolution XPS measurements of the Pd 3d and Sn 3d energy levels of the Pd2SnNRs and Pd2SnNDs prepared in step one of Example 1.

[0031] Figure 9 The graph shows the photothermal stability of Pd2Sn-SPNRs aqueous solution. a represents the photothermal conversion efficiency, and b represents the temperature change during thermal cycling.

[0032] Figure 10 The fitted curves are for the mass extinction coefficients of the soybean phospholipid-modified palladium-tin intermetallic compounds prepared in Example 1. 1 represents Pd2Sn-SPNRs, and 2 represents Pd2Sn-SPNDs.

[0033] Figure 11 The zeta potentials of Pd2Sn NRs prepared in step one and Pd2Sn-SPNRs prepared in step two of Example 1 are shown.

[0034] Figure 12The UV-vis-NIR absorption spectra of Pd2Sn-SPNRs aqueous solution and Pd2Sn-SPNDs aqueous solution are shown. 1 represents a concentration of 400 μg / mL, 2 represents a concentration of 300 μg / mL, 3 represents a concentration of 200 μg / mL, 4 represents a concentration of 100 μg / mL, 5 represents a concentration of 50 μg / mL, and 6 represents a concentration of 25 μg / mL.

[0035] Figure 13 ESR images of Pd2Sn-SPNRs prepared in Example 1, where a represents the detection... 1 O2, b represents the detection of ·OH;

[0036] Figure 14 The UV-Vis absorption spectra of Pd2Sn-SPNRs prepared in Example 1 under different conditions for catalytic oxidation of OPD and TMB are shown. a is OPD, b is TMB, 1 is Pd2Sn-SPNRs + hydrogen peroxide + laser irradiation, 2 is Pd2Sn-SPNRs + hydrogen peroxide, 3 is the laser irradiation group alone, and 4 is the control group.

[0037] Figure 15 Michaelis-Menten kinetic analysis images and Lineweaver-Burk peroxidase simulated activity images of Pd2Sn-SP LNRs, Pd2Sn-SPNRs, Pd2Sn-SP SNRs and Pd2Sn-SPNDs prepared in Example 1. a is the Michaelis-Menten image, b is the Lineweaver-Burk image, 1 is Pd2Sn-SP LNRs, 2 is Pd2Sn-SPNRs, 3 is Pd2Sn-SP SNRs, and 4 is Pd2Sn-SPNDs.

[0038] Figure 16 The oxidase-like activities of Pd2Sn-SP NRs prepared in Example 1 at different times are shown in Figure 1 (10 min, 2 8 min, 3 6 min, 4 4 min, 5 2 min).

[0039] Figure 17 Images showing the degradation of methylene blue (MB) catalyzed by Pd2Sn-SPNRs prepared in Example 1 at different time points: 1 = 0 min, 2 = 2 min, 3 = 4 min, 4 = 6 min, 5 = 8 min, and 6 = 10 min.

[0040] Figure 18 Pd₂Sn-SPNRs prepared for Example 1 were tested at different concentrations and under 808nm laser light (0.8W / cm²). 2The catalase-like activities under irradiation conditions are shown in the following figures: a) catalase activities of Pd2Sn-SPNRs at different concentrations: 1 = 400 μg / mL, 2 = 200 μg / mL, 3 = 100 μg / mL, 4 = 50 μg / mL, and 5 = pure water; b) the effect of laser irradiation on catalase-like activities of Pd2Sn-SPNRs: 1 = 200 μg / mL, 2 = 200 μg / mL + 808 nm laser irradiation.

[0041] Figure 19 The palladium-tin intermetallic compounds with different morphologies prepared in Example 1 exhibited catalase-like activities under laser irradiation: 1 = 400 μg / mL, 2 = 200 μg / mL, 3 = 100 μg / mL, 4 = 50 μg / mL, and 5 = pure water.

[0042] Figure 20 The effect of Pd2Sn-SPNRs prepared in Example 1 on cell viability when co-incubated with normal cells (L929 cells) at different concentrations for 12h and 24h. Detailed Implementation

[0043] Specific Implementation Method 1: This implementation method is a method for preparing a palladium-tin intermetallic compound with controllable morphology, which is carried out according to the following steps:

[0044] I. Preparation of Palladium-Tin Intermetallic Compounds by High-Temperature Pyrolysis:

[0045] Under magnetic stirring, oleylamine, methylamine hydrochloride, palladium acetylacetone, and tin acetate were mixed uniformly to obtain mixed solution A. Under vacuum, mixed solution A was heated to 40℃~45℃ and kept at 40℃~45℃ for 20min~25min. The vacuum device was then turned off, nitrogen gas was introduced, and the temperature was kept at 55℃~60℃ for 30min~35min to form a homogeneous solution. Trioctylphosphine was added to the homogeneous solution, and the temperature was kept at 200℃~210℃ for 30min~35min to obtain mixed solution B. Mixed solution B was heated to 300℃~310℃ and reacted at 300℃~310℃ for 25min~30min. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, collected by centrifugation, and washed to obtain the palladium-tin intermetallic compound.

[0046] When the mass ratio of methylamine hydrochloride to tin acetate is (0-0.25):1, the palladium-tin intermetallic compound is composed of nanoparticles with a particle size of 5 nm to 10 nm.

[0047] When the mass ratio of methylamine hydrochloride to tin acetate is (0.5-0.75):1, the palladium-tin intermetallic compound is a short nanorod with a length of 30 nm to 35 nm.

[0048] When the mass ratio of methylamine hydrochloride to tin acetate is (1.25-1.5):1, the palladium-tin intermetallic compound is a nanorod with a length of 70 nm-75 nm.

[0049] When the mass ratio of methylamine hydrochloride to tin acetate is (2.5-2.75):1, the palladium-tin intermetallic compound is a nanorod with a length of 120 nm to 125 nm.

[0050] II. Surface modification of palladium-tin intermetallic compounds:

[0051] The palladium-tin intermetallic compound was dissolved in cyclohexane, and then a chloroform solution of soybean lecithin was added dropwise. The solvent was evaporated in a rotary evaporator under vacuum and at a temperature of 60℃~65℃ to obtain the soybean lecithin-modified palladium-tin intermetallic compound.

[0052] In this specific embodiment, palladium exhibits multiple oxidation states and possesses excellent catalytic performance and the ability to absorb and permeate hydrogen gas, thus demonstrating good catalytic activity and catalytic capacity for various enzymes. A palladium-tin intermetallic compound bimetallic catalyst is formed by doping palladium with tin, and the ESR image of the material under laser irradiation is used for evaluation. 1 The generation of O2 and ·OH was verified by testing its UV-vis-NIR absorption spectrum in an environment containing hydrogen peroxide. This confirmed the significant characteristic absorption of oxOPD (420 nm) or oxTMB (652 nm) and methylene blue, and demonstrated its good catalytic ability to exhibit multiple enzymes (catalase, peroxidase, and oxidase-like activities). Furthermore, its good catalytic ability was verified by measuring its maximum reaction rate (Vmax) and Michaelis-Menten constant (Km). Experiments showed that its catalytic ability could be further enhanced under laser irradiation, while exhibiting low biotoxicity.

[0053] The beneficial effects of this embodiment are:

[0054] ① In this embodiment, a palladium-tin intermetallic compound bimetallic nanozyme catalyst with controllable morphology and size was prepared, which has good catalytic performance and stability.

[0055] ② The material is obtained in one step by high-temperature pyrolysis. Palladium acetylacetonate is used as the palladium source and tin acetate is used as the tin source. By controlling the amount of methylamine hydrochloride, palladium-tin intermetallic compounds with controllable morphology are generated by reaction under high temperature conditions.

[0056] ③ Both characterization experiments and density functional theory calculations confirm that structurally ordered palladium-tin intermetallic compounds possess excellent near-infrared light absorption and various enzymatic catalytic activities (such as catalase, peroxidase, and oxidase-like activities). Comparative experiments revealed that nanorods with higher specific surface areas exhibit superior performance. Therefore, morphology-controllable palladium-tin intermetallic compounds hold promise for applications in nanobiomedical research.

[0057] ④ Tin ions in palladium-tin intermetallic compounds have a high X-ray attenuation coefficient and can be used as contrast agents in computed tomography imaging, for disease diagnosis, and for real-time monitoring of the treatment process.

[0058] Therefore, the palladium-tin intermetallic compound involved in this embodiment has controllable morphology, good stability and catalytic performance, and also has good photothermal and optical properties.

[0059] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the mass ratio of oleylamine to tin acetate in step one is (0.30-0.35):1; and the mass ratio of palladium acetylacetone to tin acetate in step one is (1.70-1.75):1. Everything else is the same as in Specific Implementation Method One.

[0060] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that the mass ratio of trioctylphosphine to tin acetate in step one is (0.30-0.35):1. Everything else is the same as in Specific Implementation Method One or Two.

[0061] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that: in step one, oleylamine, methylamine hydrochloride, palladium acetylacetone, and tin acetate are mixed at a rotation speed of 500 rpm to 600 rpm for 5 min to 10 min to obtain mixed solution A. Everything else is the same as in Specific Implementation Methods One to Three.

[0062] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that: in step one, the mixed solution A is heated to 40°C to 45°C at a heating rate of 2°C / min to 3°C / min. Everything else is the same as in Specific Implementation Methods One to Four.

[0063] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that: in step one, the mixed solution B is heated to 300℃ to 310℃ at a heating rate of 2℃ / min to 3℃ / min. Everything else is the same as in Specific Implementation Methods One to Five.

[0064] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that the washing described in step one involves alternating washing with ethanol and chloroform. Everything else is the same as in Specific Implementation Methods One to Six.

[0065] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that the mass ratio of cyclohexane to the palladium-tin intermetallic compound in step two is (790-795):1. Everything else is the same as in Specific Implementation Methods One to Seven.

[0066] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that the mass ratio of soybean lecithin to palladium-tin intermetallic compound in the chloroform solution of soybean lecithin described in step two is (6.0-6.5):1. Everything else is the same as in Specific Implementation Methods One to Eight.

[0067] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Methods One to Nine in that the concentration of soybean lecithin in the chloroform solution of soybean lecithin mentioned in step two is 1 mg / mL to 1.5 mg / mL. Everything else is the same as in Specific Implementation Methods One to Nine.

[0068] The beneficial effects of the present invention are verified using the following embodiments:

[0069] Example 1, combined with Figure 1 Detailed explanation:

[0070] A method for preparing a palladium-tin intermetallic compound with controllable morphology, comprising the following steps:

[0071] I. Preparation of Palladium-Tin Intermetallic Compounds by High-Temperature Pyrolysis:

[0072] Oleylamine, methylamine hydrochloride, palladium acetylacetone (Pd(acac)2), and tin acetate (Sn(OAc)2) were mixed for 10 min at 500 rpm to obtain mixed solution A. Under vacuum, mixed solution A was heated to 40°C at a heating rate of 2°C / min and held at 40°C for 20 min. The vacuum device was then turned off, nitrogen gas was introduced, and the mixture was held at 60°C for 30 min to form a homogeneous solution. Trioctylphosphine was added to the homogeneous solution, and the mixture was held at 200°C for 30 min to obtain mixed solution B. Mixed solution B was heated to 300°C at a heating rate of 2°C / min and reacted at 300°C for 30 min. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, collected by centrifugation, and washed alternately with ethanol and chloroform to obtain the palladium-tin intermetallic compound.

[0073] The mass ratio of oleylamine to tin acetate is 0.305:1; the mass ratio of palladium acetylacetone to tin acetate is 1.717:1; and the mass ratio of trioctylphosphine to tin acetate is 0.30:1.

[0074] When the mass ratio of methylamine hydrochloride to tin acetate is 0:1, the palladium-tin intermetallic compound is palladium-tin intermetallic compound nanodots (Pd2SnNDs) with a particle size of 5nm to 10nm.

[0075] When the mass ratio of methylamine hydrochloride to tin acetate is 0.634:1, the palladium-tin intermetallic compound is a palladium-tin intermetallic compound nanorod (Pd2Sn SNRs) with a length of 30nm to 35nm.

[0076] When the mass ratio of methylamine hydrochloride to tin acetate is 1.269:1, the palladium-tin intermetallic compound is a palladium-tin intermetallic compound nanorod (Pd2SnNRs) with a length of 70nm to 75nm.

[0077] When the mass ratio of methylamine hydrochloride to tin acetate is 2.537:1, the palladium-tin intermetallic compound is a palladium-tin intermetallic compound nanorod (Pd2Sn LNRs) with a length of 120nm to 125nm.

[0078] II. Surface modification of palladium-tin intermetallic compounds:

[0079] Palladium-tin intermetallic compounds were dissolved in cyclohexane, and then a chloroform solution of soybean lecithin was added dropwise. The solvent was evaporated in a rotary evaporator under vacuum and at a temperature of 60°C to obtain soybean lecithin-modified palladium-tin intermetallic compounds, namely Pd2Sn-SPNDs, Pd2Sn-SP SNRs, Pd2Sn-SPNRs and Pd2Sn-SP LNRs.

[0080] The mass ratio of the cyclohexane to the palladium-tin intermetallic compound is 790:1;

[0081] The mass ratio of soybean lecithin to palladium-tin intermetallic compound in the chloroform solution of the soybean lecithin is 6.5:1.

[0082] The concentration of soybean lecithin in the chloroform solution is 1 mg / mL.

[0083] Figure 2 TEM images and elemental mapping images of Pd2Sn NDs and Pd2Sn NRs prepared in step one of Example 1 at different magnifications; Figure 3 The images show TEM images and elemental mapping images of Pd₂Sn SNRs and Pd₂Sn LNRs prepared in step one of Example 1 at different magnifications. Figure 2 and Figure 3It is evident that methylamine hydrochloride plays a crucial role in controlling the morphology of palladium-tin intermetallic compounds. The figure includes transmission electron microscopy (TEM) images and elemental mapping diagrams of palladium-tin intermetallic compounds of different sizes. The palladium-tin intermetallic compounds exhibit uniform and controllable morphologies and uniform distribution of corresponding elements, confirming the successful construction of intermetallic compounds with different morphologies. The particle size of Pd₂Sn NDs is 5 nm to 10 nm; the length of Pd₂Sn SNRs is 30 nm to 35 nm; the length of Pd₂Sn NRs is 70 nm to 75 nm; and the length of Pd₂Sn LNRs is 120 nm to 125 nm.

[0084] Figure 4 High-resolution transmission electron microscopy (TEM) images and lattice spacing measurements of the Pd₂Sn NRs and Pd₂Sn NDs prepared in step one of Example 1 are shown in the figures. As can be seen from the figures, the interfacial lattice spacings of the Pd₂Sn NRs and Pd₂Sn NDs are 0.195 nm and 0.236 nm, respectively, corresponding to the (320) and (021) orthorhombic crystal planes.

[0085] Figure 5 The figure shows the EDS spectrum of the Pd₂Sn NRs prepared in step one of Example 1. As can be seen from the figure, the molar ratio of palladium to tin is 2:1, confirming the successful preparation of the palladium-tin intermetallic compound.

[0086] Figure 6 The images show the PXRD patterns of Pd₂Sn NDs, Pd₂Sn SNRs, Pd₂Sn NRs, and Pd₂Sn LNRs prepared in step one of Example 1. a) shows Pd₂Sn NRs and Pd₂Sn NDs, b) is a magnified view of a), and c) shows Pd₂Sn LNRs and Pd₂Sn SNRs. As can be seen from the figures, their diffraction peaks all exhibit good crystallinity and can match the diffraction peaks of the pure orthorhombic Pd₂Sn phase (PDF00-026-1297), and their lattice parameters are all... It exhibits a coppernite structure.

[0087] Figure 7 The XPS spectra of Pd₂SnNRs and Pd₂SnNDs prepared in step one of Example 1 are shown in the figure. As can be seen from the figure, the prepared palladium-tin intermetallic compounds are mainly composed of Pd and Sn elements.

[0088] Figure 8 High-resolution XPS measurements of the Pd 3d and Sn 3d energy levels of the Pd₂SnNRs and Pd₂SnNDs prepared in step one of Example 1 are shown. As can be seen from the figure, the palladium 3d energy level can be a spin-splitting orbital 3d. 3 / 2 and 3D 5 / 2The binding energies at 341.4 eV and 336.1 eV are attributed to Pd. 2+ The peak values ​​at 340.6 eV and 335.3 eV were assigned to Pd0, confirming the presence of Pd0 in Pd2Sn NRs. 2+ Pd(76%) and Pd0(24%) coexist, while Pd2Sn NDs contain Pd 2+ (64%) and Pd0 (36%) coexist. Meanwhile, the high-resolution XPS spectrum of the Sn 3d phase of the Pd2Sn intermetallic compound shows obvious decomposition, verifying the presence of tin with two different valence states, at 495.3 eV (3d). 5 / 2 ) and 486.8eV (3d 3 / 2 The peak at ) and Sn 4+ Related, and at 493.8 eV (3d 5 / 2 ) and 485.3eV (3d 3 / 2 The peak at ) and Sn 2+ These results confirm that Pd₂Sn intermetallic compounds can generate more reactive oxygen species (ROS) through redox reactions.

[0089] Using an 808nm laser (0.8W / cm) 2 The Pd₂Sn-SPNRs aqueous solution with a concentration of 200 μg / mL was continuously irradiated for four cycles to explore its photothermal stability, and the temperature changes during the thermal cycling were plotted. Figure 9 b). Select the cooling curve of the first cycle and calculate the photothermal conversion efficiency (η) of the Pd2Sn-SP aqueous solution (n). Figure 9 a). Figure 9 The graph shows the photothermal stability of Pd₂Sn-SPNRs aqueous solution. a represents the photothermal conversion efficiency, and b represents the temperature change during thermal cycling. Figure 9 As can be seen from this, Pd₂Sn-SPNRs exhibit good photothermal conversion efficiency. Besides the photothermal conversion capability, photothermal stability is also crucial to the photothermal conversion process, and this was further evaluated through four on / off laser power cycles. After four cycles of heating and natural cooling, the temperature showed no significant change, indicating that they possess high photothermal stability. Figure 9 b). Based on the cooling curve, the photothermal conversion efficiency (η) of Pd₂Sn-SPNRs was calculated to be 41.2% ( Figure 9 a).

[0090] Statistical analysis of absorbance values ​​at 808 nm for different concentrations of soybean phospholipid-modified palladium-tin intermetallic compounds in UV-vis-NIR absorption spectroscopy. Figure 12(The absorbance values ​​at 808 nm for each curve) are used to plot the mass extinction coefficient of the palladium-tin intermetallic compound modified with soybean phospholipids. The slope of the fitted curve is its extinction coefficient a. Figure 10 The figure shows the fitting curves of the mass extinction coefficients of the soybean phospholipid-modified palladium-tin intermetallic compounds prepared in Example 1. Figure 1 represents Pd₂Sn-SPNRs, and Figure 2 represents Pd₂Sn-SPNDs. As can be seen from the figure, the absorbance of both Pd₂Sn-SPNDs and Pd₂Sn-SPNRs increases linearly with increasing concentration. The extinction coefficient of Pd₂Sn-SPNRs is a = 5.33 L / g. -1 cm -1 The extinction coefficient of Pd2Sn-SPNDs is a = 2.30 L g. - 1 cm -1 From the extinction coefficient perspective, Pd2Sn-SPNRs (5.33L g) -1 cm -1 ) compared to Pd2Sn-SPNDs (2.30 L g) -1 cm -1 It has stronger absorption.

[0091] To improve the biocompatibility of Pd2Sn intermetallic compounds, a palladium-tin intermetallic compound modified with soybean phospholipids was prepared. Figure 11 The figure shows the zeta potentials of the Pd₂Sn NRs prepared in step one and the Pd₂Sn-SPNRs prepared in step two of Example 1. As can be seen from the figure, after SP functionalization, the zeta potential changes from 0.13mV to -29.93mV.

[0092] The Pd2Sn-SPNRs and Pd2Sn-SPNDs prepared in Example 1 were dispersed in water and subjected to UV-vis-NIR absorption spectroscopy tests. Figure 12 The figures show the UV-vis-NIR absorption spectra of aqueous solutions of Pd₂Sn-SPNRs and Pd₂Sn-SPNDs. 1 represents a concentration of 400 μg / mL, 2 represents 300 μg / mL, 3 represents 200 μg / mL, 4 represents 100 μg / mL, 5 represents 50 μg / mL, and 6 represents 25 μg / mL. As can be seen from the figure, the absorbance intensity of both Pd₂Sn-SPNRs and Pd₂Sn-SPNDs increases linearly with increasing concentration.

[0093] Qualitative evaluation was performed using 2,2,6,6-tetramethylpiperidine (TEMP) and 5,5-dimethyl-1-pyrrolidine-N-oxide (DMPO) as trapping agents, via electron spin resonance (ESR) measurements. 1 The formation of O2 and ·OH was observed. TEMP was used as a decoy to detect ·OH.1 O2( Figure 13 a) Mix the Pd2Sn-SPNRs aqueous solution (100 μL, 1 mg / mL) prepared in Example 1, PBS (340 μL, pH = 5.5), and 2,2,6,6-tetramethylpiperidine (TEMP) (10 μL). For the hydrogen peroxide group, hydrogen peroxide should be added via rapid injection (100 mM, 50 μL). For the laser irradiation group, use an 808 nm laser (0.8 W / cm²). 2 Irradiation; using DMPO as a decoy, detection of ·OH( Figure 13 b): The Pd2Sn-SP NRs aqueous solution (100 μL, 1 mg / mL) prepared in Example 1, PBS (340 μL, pH = 5.5), and 5,5-dimethyl-1-pyrrolidinyl-N-oxide (DMPO) (10 μL) were mixed, and hydrogen peroxide (100 mM, 50 μL) was rapidly injected. The solution was then analyzed using electron paramagnetic resonance spectroscopy. The laser irradiation group used an 808 nm laser (0.8 W / cm²). 2 Irradiation. Figure 13 ESR images of Pd2Sn-SPNRs prepared in Example 1, where a represents the detection... 1 O2, b represents the detection of ·OH. (From...) Figure 13 As can be seen from a, when Pd2Sn-SPNRs are irradiated with an 808nm laser, ... 1 The O2 signal peaks were clearly 1:1:1, and the signal was even stronger after the addition of hydrogen peroxide, indicating the production of... 1 O2. In Figure 13 In b, a distinct quadruple resonance peak of ·OH with a signal intensity ratio of 1:2:2:1 can be observed, verifying the generation of ·OH. At the same time, the quadruple resonance peak signal will be enhanced under 808nm laser irradiation.

[0094] 3 mL of a phosphate buffer solution (pH = 5.5) containing 300 μg / mL LTMB (or OPD) and 100 μg / mL Pd₂Sn-SPNRs was mixed with hydrogen peroxide to achieve a hydrogen peroxide concentration of 50 mM. The absorbance intensity of each group was recorded after a certain reaction time. The laser irradiation group used an 808 nm laser (0.8 W / cm²). 2 The control group was irradiated with hydrogen peroxide, while the control group was not irradiated with laser. Figure 14The UV-Vis absorption spectra of Pd2Sn-SPNRs prepared in Example 1 under different conditions for the catalytic oxidation of OPD and TMB are shown. a represents OPD, b represents TMB, 1 represents Pd2Sn-SPNRs + hydrogen peroxide + laser irradiation, 2 represents Pd2Sn-SPNRs + hydrogen peroxide, 3 represents laser irradiation alone, and 4 represents the control group. As shown in the figure, the addition of hydrogen peroxide induced significant characteristic absorption of the oxidation products oxOPD (420 nm) or oxTMB (652 nm) in Pd2Sn-SPNRs. No changes were observed in the control group and the laser-only group. Furthermore, the absorption intensity of Pd2Sn-SPNRs increased after laser irradiation, and... Figure 13 ESR measurement results are similar.

[0095] Simulated peroxidase activity assays were performed on soybean lecithin-modified Pd₂Sn-SP nanocomposites (NDs, NRs, SNRs, and LNRs) with different morphologies. The assays were conducted using TMB as a substrate in phosphate buffered saline (PBS, pH 5.5) with H₂O₂ present. Steady-state kinetics were also performed in phosphate buffered saline (pH 5.5) with an aqueous solution of Pd₂Sn-SP nanocomposites (20 μg / mL) as a catalyst in the presence of both H₂O₂ and TMB. Simultaneously, the kinetics of Pd₂Sn-SP nanocomposites were assessed using H₂O₂ as a substrate (1, 2, 4, and 16 mM). All reactions were monitored by measuring absorbance at different reaction times, and the Michaelis-Menten constant and maximum reaction rate were calculated using the Michaelis-Menten equation.

[0096] Figure 15 The images show Michaelis-Menten kinetic analysis images and Lineweaver-Burk peroxidase simulated activity images of Pd2Sn-SP LNRs, Pd2Sn-SPNRs, Pd2Sn-SP SNRs, and Pd2Sn-SPNDs prepared in Example 1. a is the Michaelis-Menten image, b is the Lineweaver-Burk image, 1 is Pd2Sn-SP LNRs, 2 is Pd2Sn-SPNRs, 3 is Pd2Sn-SP SNRs, and 4 is Pd2Sn-SPNDs. Table 1 compares the activity kinetic parameters of the palladium-tin intermetallic compound peroxidases with different morphologies prepared in Example 1. Figure 15 Table 1 shows the differences in catalytic activity of Pd2Sn-SP nanocomposites (NDs, NRs, SNRs, and LNRs) modified with soybean phospholipids by different morphologies, as analyzed by steady-state kinetics. All activities conform to typical Michaelis-Menten kinetics. The maximum reaction rate (VL) was obtained from the Lineweaver-Burk plot. maxThe values ​​of V and the Michaelis-Menten constant (Km) are summarized in Table 1. Generally, V... max The higher K is m The lower the V, the better the catalytic performance. Taking V into account... max and K m Regarding the impact on catalytic performance, Pd2Sn-SPNRs exhibit higher catalytic efficiency compared to Pd2Sn-SPNDs. Furthermore, the catalytic efficiency is also related to the length of Pd2Sn-SPNRs; both excessively long and short lengths are detrimental to POD simulation activity.

[0097] Table 1

[0098] Nanozymes <![CDATA[Pd2Sn-SPLNRs]]> <![CDATA[Pd2Sn-SPNRs]]> <![CDATA[Pd2Sn-SPSNRs]]> <![CDATA[Pd2Sn-SPNDs]]> Substrate <![CDATA[H2O2]]> <![CDATA[H2O2]]> <![CDATA[H2O2]]> <![CDATA[H2O2]]> <![CDATA[V max (×10 -8 Ms -1 )]]> 25.28 29.35 16.63 6.69 <![CDATA[K max (mM)]]> 22.65 20.86 23.61 17.27

[0099] The absorbance intensity of each group was recorded after reacting 3 mL of phosphate buffer solution containing 300 μg / mL LTMB and 100 μg / mL Pd2Sn-SPNRs at room temperature for a certain period of time. Figure 16 The figure shows the oxidase-like simulated activity of Pd2Sn-SPNRs prepared in Example 1 at different time points: 1 for 10 min, 2 for 8 min, 3 for 6 min, 4 for 4 min, and 5 for 2 min. This figure demonstrates the OXD simulated catalytic activity of Pd2Sn-SPNRs (70 nm–75 nm) verified using TMB, showing the generation of O2. Furthermore, the absorbance at 652 nm increases with time, indicating that Pd2Sn-SPNRs possess significant OXD simulated activity and oxidizing capacity even in the absence of hydrogen peroxide.

[0100] 3 mL of an aqueous solution containing 10 μg / mL MB and 100 μg / mL Pd2Sn-SPNRs was rapidly injected into a hydrogen peroxide solution to achieve a hydrogen peroxide concentration of 50 μM. The absorbance of the mixed solution was measured at different time intervals, and the POD simulated catalytic activity of Pd2Sn-SPNRs was verified using MB. Figure 17 Images showing the degradation of methylene blue (MB) catalyzed by Pd2Sn-SPNRs prepared in Example 1 at different time points: 1 = 0 min, 2 = 2 min, 3 = 4 min, 4 = 6 min, 5 = 8 min, and 6 = 10 min. The methylene blue (MB) experiment verified the effective generation of ·OH in the presence of Pd2Sn-SPNRs, indicating that Pd2Sn-SPNRs possess high POD-simulated catalytic activity.

[0101] Figure 18 and Figure 19This study describes the catalase-like activities of Pd2Sn-SP LNRs, Pd2Sn-SPNRs, Pd2Sn-SP SNRs, and Pd2Sn-SPNDs prepared in Example 1 under different conditions and morphologies. The experiment used a dissolved oxygen analyzer to detect O2 generation induced by Pd2Sn-SP under different conditions and morphologies to evaluate the CAT-like activity: 3 mL of aqueous solutions of Pd2Sn-SP LNRs, Pd2Sn-SPNRs, Pd2Sn-SP SNRs, or Pd2Sn-SPNDs (0, 50, 100, 200, and 400 μg / mL) were mixed with hydrogen peroxide to achieve a hydrogen peroxide concentration of 50 mM. The oxygen concentration (mg / L) was continuously recorded for 6 minutes. Figure 18 Pd₂Sn-SPNRs prepared for Example 1 were tested at different concentrations and under 808nm laser light (0.8W / cm²). 2 The catalase-like activities under irradiation conditions are shown in the following figures: a) catalase activities of Pd2Sn-SPNRs at different concentrations: 1 = 400 μg / mL, 2 = 200 μg / mL, 3 = 100 μg / mL, 4 = 50 μg / mL, and 5 = pure water; b) the effect of laser irradiation on catalase-like activities of Pd2Sn-SPNRs: 1 = 200 μg / mL, 2 = 200 μg / mL + 808 nm laser irradiation. Figure 19 The palladium-tin intermetallic compounds with different morphologies prepared in Example 1 exhibited catalase-like activities under laser irradiation: 1 (400 μg / mL), 2 (200 μg / mL), 3 (100 μg / mL), 4 (50 μg / mL), and 5 (pure water). Comparison revealed that Pd₂Sn-SP NRs exhibited the strongest CAT-like catalytic activity, consistent with the results of POD-like catalytic activity. With increasing Pd₂Sn-SP NRs concentration, O₂ generation also increased, and the addition of laser light further promoted the CAT-like catalytic activity.

[0102] Figure 20 The effect of Pd2Sn-SP NRs prepared in Example 1 on cell viability after co-incubation with normal cells (L929 cells) at different concentrations for 12h and 24h is shown in the figure. As can be seen from the figure, Pd2Sn-SP NRs prepared in Example 1 showed almost no cytotoxicity after co-incubation with L929 cells for 12h and 24h, and also showed good biocompatibility even at higher concentrations.

Claims

1. A method for preparing a palladium-tin intermetallic compound with controllable morphology, characterized in that... It is done in the following steps: I. Preparation of Palladium-Tin Intermetallic Compounds by High-Temperature Pyrolysis: Under magnetic stirring, oleylamine, methylamine hydrochloride, palladium acetylacetone, and tin acetate were mixed uniformly to obtain mixed solution A. Under vacuum, mixed solution A was heated to 40℃~45℃ at a heating rate of 2℃ / min~3℃ / min and held at 40℃~45℃ for 20min~25min. The vacuum device was then turned off, nitrogen gas was introduced, and the temperature was maintained at 55℃~60℃ for 30min~35min to form a homogeneous solution. Trioctylphosphine was added to the homogeneous solution, and the temperature was maintained at 200℃~210℃ for 30min~35min to obtain mixed solution B. Mixed solution B was heated to 300℃~310℃ at a heating rate of 2℃ / min~3℃ / min and reacted at 300℃~310℃ for 25min~30min. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, collected by centrifugation, and washed to obtain the palladium-tin intermetallic compound. The mass ratio of oleylamine to tin acetate is (0.30~0.35):1; the mass ratio of palladium acetylacetone to tin acetate is (1.70~1.75):1; the mass ratio of trioctylphosphine to tin acetate is (0.30~0.35):

1. The lattice parameters of the palladium-tin intermetallic compound are a = 8.11 Å, b = 5.662 Å, c = 4.234 Å, and the palladium-tin intermetallic compound has a pyrite structure. When the mass ratio of methylamine hydrochloride to tin acetate is (0~0.25):1, the palladium-tin intermetallic compound is composed of nanoparticles with a particle size of 5nm~10nm. When the mass ratio of methylamine hydrochloride to tin acetate is (0.5~0.75):1, the palladium-tin intermetallic compound is a short nanorod with a length of 30nm~35nm; When the mass ratio of methylamine hydrochloride to tin acetate is (1.25~1.5):1, the palladium-tin intermetallic compound is a nanorod with a length of 70nm~75nm; When the mass ratio of methylamine hydrochloride to tin acetate is (2.5~2.75):1, the palladium-tin intermetallic compound is a nanorod with a length of 120nm~125nm; II. Surface modification of palladium-tin intermetallic compounds: The palladium-tin intermetallic compound was dissolved in cyclohexane, and then a chloroform solution of soybean lecithin was added dropwise. The solvent was evaporated in a rotary evaporator under vacuum and at a temperature of 60℃~65℃ to obtain the soybean lecithin-modified palladium-tin intermetallic compound.

2. The method for preparing a morphology-controllable palladium-tin intermetallic compound according to claim 1, characterized in that... In step one, oleylamine, methylamine hydrochloride, palladium acetylacetone and tin acetate are mixed at a speed of 500 rpm to 600 rpm for 5 min to 10 min to obtain mixed solution A.

3. The method for preparing a morphology-controllable palladium-tin intermetallic compound according to claim 1, characterized in that... The washing described in step one involves alternating between ethanol and chloroform.

4. The method for preparing a morphology-controllable palladium-tin intermetallic compound according to claim 1, characterized in that... The mass ratio of cyclohexane to palladium-tin intermetallic compound in step two is (790~795):

1.

5. The method for preparing a morphology-controllable palladium-tin intermetallic compound according to claim 1, characterized in that... In step two, the mass ratio of soybean lecithin to palladium-tin intermetallic compound in the chloroform solution of soybean lecithin is (6.0~6.5):

1.

6. The method for preparing a morphology-controllable palladium-tin intermetallic compound according to claim 1, characterized in that... The concentration of soybean lecithin in the chloroform solution of soybean lecithin mentioned in step two is 1 mg / mL to 1.5 mg / mL.

Citation Information

Patent Citations

  • Apolipoprotein modified fusion type multifunctional nano vesicle, and preparation method and application thereof

    CN113616811A